First Report of Proteocephalus longicollis (Zeder, 1800) in Alosa fallax lacustris (Fatio, 1890) from Lake Garda (Italy): Morphological and Molecular Study - Ivan Corti; Giovanni De Benedetto; Kristian Riolo; Renato Malandra; Gabriella Gaglio (Veterinary Sciences, 2023)
Twaite shad (Alosa fallax) includes two subspecies, the anadromous Alosa fallax nilotica, and the landlocked species Alosa fallax lacustris, representing the only Clupeidae inhabiting Lake Garda. Study of the parasitic fauna of this species in this area is still limited. For this reason, the aim of the present study was to evaluate the presence of tapeworms from A. fallax lacustris sampled in Lake Garda. Sixty-six A. fallax lacustris specimens were collected at the Milan fish market (Lombardy, Italy); specifically, an evaluation of the gastrointestinal contents was carried out for the presence of helminths. All parasites found were fixed in 70% ethanol and transferred to the laboratories of the University of Messina for morphological and molecular analysis. Parts of the parasites were stained with Semichon’s carmine red technique. Molecular analysis was carried out using LSU rRNA and ITS2 region genes. Eight specimens out of sixty-six (12.1%) were positive for adult cestodes within the pyloric caeca. Morphological and molecular analysis could to identify the parasites found to be Proteocephalus longicollis. This parasite species is not considered a zoonotic agent, representing a low risk of parasitic fish-borne zoonosis for consumers of this appreciated fish from Lake Garda.